FORMATION OF PROFESSIONAL FEATURES OF THE TEACHER IN THE CONDITIONS OF HIGHER SCHOOL - L.V. Kondrashova (Academy of Cognitive and Natural Sciences, 2022)
The essence of the professional aspect of a contemporary teacher, his main characteristics, and ways of his making under conditions of higher pedagogical school are disclosed in this article.